Developing an Integrated E-Module on Religious Moderation to Address Rising Radicalism in Schools: Implications for Students’ Understanding - Minhaji; Akhmad Nurul Kawakip; Moh Nawafil; Junaidi; Asmuki (Jurnal Pendidikan Agama Islam, 2025)
Purpose – Despite national efforts to advance religious moderation, schools still lack digital IRE (Islamic Religious Education) materials, while adolescents increasingly encounter unregulated online content. This makes moderation-focused resources urgently needed. This study aims to develop and assess the IRE e-module’s effectiveness in improving students’ understanding of religious moderation. Design/methods/approach – The study employed a Research and Development design using the 4D model, including define, design, develop and dissemination. The research subjects consisted of 84 junior high school students across three schools in Situbondo. Data were collected through interviews, observations, documentation, questionnaires, and tests. Findings – Validation results from 3 experts show that the e-module has met the eligibility standards with a minimum score of 80%. The effectiveness test showed a significant increase in student understanding after using the e-module with Sig. [2 Tailed] = 0,000 and an average N-Gain of 0,6693.  An integrated E modul on religiuos moderation to Address Rising Radicalism in Schools: Implications for Students’ Understanding” Research implications/limitations – The practical implications of this research provide a strategic contribution to developing relevant contextual teaching materials to prevent the spread of radicalism in secondary education. However, this study has limitations regarding the level and number of schools studied. Originality/value – The study advances IRE digital material by demonstrating multimedia tools that foster moderation, provides a replicable resource for IRE teachers, and informs efforts to strengthen learning and counter extremist narratives.